Inclusiveness of Additional Support and Assistance for Students - Jeznik, Katja (Revija za elementarno izobraževanje, 2022)
Research shown that solutions for children with special education needs are successful in improving their academic performance, but less successful in improving their social inclusion. This article presents a case study of additional support from mobile special and rehabilitation educators for students who need extra encouragement to achieve their goals but are not identified as children with special needs. The research focus was understanding of inclusion and identifying overlapping activities with established practices. A patchy understanding of inclusion was found and a focus on working differently with students. Despite the encouraging findings, designing inclusive practices stays a major challenge.
Keywords: additional support and assistance, inclusion, mobile special rehabilitation educator, learning difficulties